Endometriosis Is a Cause of Infertility. Does Reactive Oxygen Damage to Gametes and Embryos Play a Key Role in the Pathogenesis of Infertility Caused by Endometriosis? - Máté, Gábor; Bernstein, Lori R.; Török, Attila L. (Frontiers in Endocrinology, 2018)
Approximately, 10–15% of women of reproductive age are affected by endometriosis, which often leads to infertility. Endometriosis often has an inherited component, and several causative predisposing factors are hypothesized to underlie the pathogenesis of endometriosis. One working hypothesis is the theory of retrograde menstruation. According to the theory of retrograde menstruation, components of refluxed blood, including apoptotic endometrial tissue, desquamated menstrual cells, lysed erythrocytes, and released iron, induce inflammation in the peritoneal cavity. This in turn activates macrophage release of reactive oxygen species (ROS), leading to oxidative stress via the respiratory burst. Refluxed blood promotes the Fenton reaction, terminating in the production of hydroxyl radical, the most potently destructive ROS. In this article, we review the papers that demonstrate decreased quantity and quality of oocytes and embryos retrieved from IVF/ICSI patients with endometriosis. We discuss literature data demonstrating that ROS are generated in endometriotic tissues that have physical proximity to gametes and embryos, and demonstrating adverse impacts on oocyte, sperm and embryo microtubule apparatus, chromosomes, and DNA. Data that addresses the notions that endometriosis causes oocyte and fetal aneuploidy and that these events are mediated by ROS species are also discussed. Literature data are also discussed that employ use of anti-oxidant molecules to evaluate the importance of ROS-mediated oxidative damage in the pathogenesis of endometriosis. Studies are discussed that have employed anti-oxidants compounds as therapeutics to improve oocyte and embryo quality in infertile subjects, and improve fertility in patients with endometriosis.